Problematika Implementasi Merdeka Belajar Kampus Merdeka (MB-KM) Di PTKIS IV Surabaya - Fajar Indarsih (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
One of the nine MB-KM programs that PTKIS constitutes is student exchanges, and operational costs. In principle, PTKIS in the Pesantren environment is different from campuses outside boarding. Tuition fees at PTKIS adjust to the economic conditions of the surrounding community and the economic conditions of students. In this paper, it is concluded that the problem of implementing the MB-KM program at PTIKS focuses on two things, first is the size of students or student exchanges, and secondly operational costs. Resolution in the problem of MB-KM implementation within PTKIS IV Surabaya through MoU and MoA MB-KM Santri Exchange. MoU and MoA MB-KM Santri Exchange contains an agreement between universities in horseshoe to realize student exchanges with student status as a solution to the main problem of MB-KM realization at PTKIS.